PERFORMANCE EVALUATION AND INDICES OF CYBER CAFÉ BUSINESS: A FACTOR ANALYTIC APPROACH (Journal of Information and Communication Technology, 2008)
The advent of the World Wide Web has opened up a new vista of opportunities for investment in the Information Communication Technology (ICT) industry. In recent years, the cyber café business has attracted considerable investment, providing job opportunities for many people. On the other hand, it has also been observed that some hitherto vibrant cyber cafes are also closing down due to the fact that they could not break even. This study, is therefore, aimed at identifying the factors/indices that could enhance the performance of cyber cafes. A total of 250 users of cyber cafes in Akure, Ondo State, Nigeria were randomly selected and a structured questionnaire was administered on them. Data collected was analysed using factor analysis by principal component. The result revealed that four factors, namely quality of hardware, speed of processing, cost, and reliability of service are the major factors that influence users’ patronage. It is therefore recommended that investors and would-be-investors in the cyber cafe business should pay attention to these facors in order to enhance the success of their investment.